PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTARISTIK PEKERJAAN TERHADAP PERILAKU TIDAK AMAN (UNSAFE ACTION) PADA PEKERJA DIVISI KAPAL NIAGA PT. PAL INDONESIA TAHUN 2018 - Friska Ayu; Muslikha Nourma Rhomadhoni (UNUSA Press, 2019)
The accident that occurred was caused by two factors like unsafe act and unsafe condition. PT PAL is one of the companies that produce ships and provides ship maintenance services which every process have pontential hazard like welding process, grinding process and steel cutting process. Initial survey showed there was several accident like pinched causing minor injuries and some nearmiss to workers in the welding section. This research was conducted in Commercial Ship Division PT. PAL with aim to analyze the influence of individual characteristics and characteristics of work with unsafe act on the Commerce Division of PT. PAL using cross sectional study with total sample of as many as 80 worker. Characteristics of respondent and unsafe action was obtained from interview with workers and observation directly to the field. The result of statistical tests using binary logistic regression showed that characteristics individual and characteristics of work which has an influence on unsafe action are age (p=0,001), knowledge of OHS (p=0,000) and time periode (p=0,008) with R value = 0,690. This means that age, knowledge of OHS and time periode have an effect of 69% on unsafe action on workers in the division of the commercial ship PT. PAL (Indonesia) and 31% are influenced by other factors. Recommendation for workers should avoid unsafe act while working like joking and for the companies should be more routine to hold socialization related implementation of OSH in the workplace and also increase supervision for workers, especially in the habit of using PPE in accordance with established policies.